(untitled) (Bulletin KNOB, 2001)
Since the opening in 1885 the Amsterdam Rijksmuseum has been a controversial building. Externally it was preserved in the form designed by P.J.H. Cuypers, internally it has become a confusing labyrinth since around 1920 and even more so since 1950. Externally, in sculptures, reliëfs and tile tableaux it radiates the late nineteenth-century artistic vision. Internally too, there was an extensive iconographic programme, which critics chiefly regarded as a moralistic and pedantic plea for the elevation of the people. This interior, though it must have been lighter and brighter in colour than old photographs lead one to suspect, was seriously affected by the building-over of the courtyards and the removal of practically all the decorations. Thus the original, clear structure was lost. In the coming restoration and conversion the building should be seen as a museum piece and a monument of the late nineteenth-century conceptions about the museum. It deserves a careful and reversible approach, based on thorough research. Then it will be possible to recapture the qualities of the theatrical sequence of stairs, galleries and museum rooms.